Cell lineage-specific mitochondrial resilience during mammalian organogenesis - Burr, Stephen P.; Klimm, Florian; Glynos, Angelos; Prater, Malwina; Sendon, Pamella; Nash, Pavel; Powell, Christopher A.; Simard, Marie-Lune; Bonekamp, Nina A.; Charl, Julia; Diaz, Hector; Bozhilova, Lyuba V.; et al. (Cell, 2023)
Mitochondrial activity differs markedly between organs, but it is not known how and when this arises. Here we show that cell lineage-specific expression profiles involving essential mitochondrial genes emerge at an early stage in mouse development, including tissue-specific isoforms present before organ formation. However, the nuclear transcriptional signatures were not independent of organelle function. Genetically disrupting intra-mitochondrial protein synthesis with two different mtDNA mutations induced cell lineage-specific compensatory responses, including molecular pathways not previously implicated in organellar maintenance. We saw downregulation of genes whose expression is known to exacerbate the effects of exogenous mitochondrial toxins, indicating a transcriptional adaptation to mitochondrial dysfunction during embryonic development. The compensatory pathways were both tissue and mutation specific and under the control of transcription factors which promote organelle resilience. These are likely to contribute to the tissue specificity which characterizes human mitochondrial diseases and are potential targets for organ-directed treatments.
Online verfügbar: 23. Februar 2023,Artikelversion: 16. März 2023
Gesehen am 24.06.2024